High-ZT half-Heusler thermoelectrics, Ti0.5Zr0.5NiSn and Ti0.5Zr0.5NiSn0.98Sb0.02: Physical properties at low temperatures. (March 2019) - Rogl, G.; Yubuta, K.; Romaka, V.V.; Michor, H.; Schafler, E.; Grytsiv, A.; Bauer, E.; Rogl, P.
Abstract: With a small gap in the density of states and a substantially semiconducting behavior half Heusler alloys have drawn attention as thermoelectric materials. For this study we have selected Hf-free compounds, Ti0.5 Zr0.5 NiSn, Ti0.5 Zr0.5 NiSn (with a densification aid (DA)) and Ti0.5 Zr0.5 NiSn0.98 Sb0.02 as well their parent alloys TiNiSn and ZrNiSn as cheap thermoelectrics. Electrical resistivity, thermal conductivity and specific heat were evaluated below room temperature (4.2–300 K) in order to get insight into the mechanism of transport properties. SEM and TEM investigations as well as DFT (density functional theory) calculations accompany this research. The fine-grained epitaxial microstructure with a large number of dislocations warrants a low thermal conductivity at ultralow values (∼30 mW/cmK at 300 K) at a narrow band gap with a sufficiently high density of states at the Femi level. High order of components mixing strongly affects the stability of the solid solutions by the configuration entropy term, which causes a shrinkage of the miscibility gap. For the electronic density of states (DOS) the split Zr band and impurity Ni band induce a significant reduction of the effective energy gap and thus explain n-type of conductivity of the compounds and solid solutions studied. Graphical abstract: Image 1